Enterprise Architecture: A Strategy to Achieve e-Government Dimension of Smart Village Using TOGAF ADM 9.2 - Ilham Alhari, Muhammad; Nur Fajrillah, Asti Amalia (Society of Visual Informatics, 2022)
Transformation in village government with the enterprise architecture smart village design model is significant for developing digital technology in the village government environment to realize a government with aspects of integrity values that are in synergy with the SDGs sustainable development goals. The method used in this study uses the adoption of the TOGAF ADM 9.2 framework, which consists of five phases: Preliminary, Architecture vision, Business architecture, Data architecture, Application architecture, while determining the clustering of villages by taking into account several aspects of the assessment released directly by the Ministry of Village, The Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia in the form of a village index building the IDM which aims to identify and facilitate analysis of village capabilities and the characteristics of village government at each level. The output produced in this study is in the form of an enterprise architecture smart village design that will assist the village government in describing a target in the form of a digital development design on the e-Government dimension in the form of several application platforms covering various management of public administration services, public development aspirations, and management. Village development, as well as the management of village government documents. From a village sample that was used as the object of research with the value of the advanced village clustering index according to the Village Index data, the IDM was built so that the smart village design concept and the synergy of the SDGs development goals